Implementasi Nilai-Nilai Multikultural Pada Pembelajaran Pendidikan Agama Islam Dalam Menumbuhkan Sikap Toleransi Beragama di SMA Katolik Santo Paulus Jember - Jannah, Khairiyatul (IJIT: Indonesian Journal of Islamic Teaching, 2025)
In the context of Indonesia's multicultural society, education that promotes multicultural values is an essential necessity. Multicultural education aims to shape students to be able to accept and appreciate diversity in terms of culture, ethnicity, language, and religion. Multicultural Islamic education is understood as a learning process that upholds the principles of democracy, equality, and justice, and is oriented toward the values of humanity, togetherness, and peace. This study uses a descriptive qualitative approach with research subjects including the principal, Islamic Education (PAI) teachers, religious studies teachers, as well as Muslim and non-Muslim students at Santo Paulus Catholic Senior High School in Jember. Data collection techniques include passive participant observation, in-depth interviews, and documentation. Data analysis involves the stages of data collection, condensation, display, and conclusion drawing, while data validity isensured through prolonged observation, increased persistence, and triangulation. The results of the study indicate that multicultural values in PAI learning are implemented to foster tolerance, both among fellow Muslims and between followers of different religions. Internal religious tolerance is developed through activities such as congregational prayers, recitation of short Qur'anic chapters, classroom discussions, as well as the use of Islamic greetings and reminders to perform worship. Meanwhile, interreligious tolerance is built through giving advice that emphasizes respect for religious differences, cross-religious support during religious celebrations, and joint activities such as visits to houses of worship and interfaith gatherings that promote freedom of religion according to each individual's beliefs. Keyword: Multicultural Values, Religious Tolerance